Nivel de conocimiento sobre el sistema de suministro de medicamentos en los estudiantes del XI ciclo del semestre 2015-I de Farmacia y Bioquímica de la Universidad Nacional de Trujillo - 2015 - Fernández Vargas, Erika Joana (2015)
This research aims to determine the level of knowledge of students enrolled in the XI cycle 2015-I Semester of Pharmacy and Biochemistry of the National University of Trujillo, on Drug Delivery System. To measure knowledge, it was used as an instrument a questionnaire validated by a panel of experts, this instrument contains two sections, the first with general data such as age, sex and attitude questions, and the second with 21 knowledge questions. This instrument was applied to 89 students, and for evaluation scale interval measurement was used by the formula ±δ; the information was analyzed using frequency tables with an entry absolute and relative values. The 46.07% of the students surveyed had a good level of overall knowledge of the drug supply system; the 53.93% of these students had an acceptable level. With regard to knowledge of the regulations of drug supply, the 46.07% of the students had an acceptable level, the 35.96% of students a solid level and 17.98% of students a low level. Regarding the stages, a higher percentage with a solid level in the selection steps 56.18 % and 53.93 % in the use step were obtained; with an acceptable level in the stages of storage and distribution with 65,17 % and 66,29 % respectively; and a low level in the step of acquiring with 31,46 % .In conclusion the students of XI cycle 2015-I Semester of Pharmacy and Biochemistry of the National University of Trujillo have an acceptable level of knowledge, because of basic training on drug supply